The Minimally Invasive Bipolar Fixation for Pediatric Spinal Deformities: A Narrative Review - Lotfi Miladi; Federico Solla; Mathilde Gaume (MDPI AG, 2024)
Growing rod techniques are increasingly used for early-onset scoliosis in children. Unfortunately, they are associated with many complications, particularly neuromuscular scoliosis, favored by the poor general condition of these patients and the fragility of their osteoporotic bones. Furthermore, these interventions are often iterative and usually followed by vertebral fusion at the end of growth. This is a review of the literature on a recent fusionless technique, minimally invasive bipolar fixation, which is more stable than the traditional growing rod techniques and less aggressive than vertebral arthrodesis. It allows the avoidance of arthrodesis, owing to the solidity of the construct and the stability of the results, leading to progressive spinal stiffening that occurs over time. The results of this technique have been published with a long follow-up period and have confirmed that it can completely replace posterior vertebral arthrodesis, especially in the most complicated scoliosis. Because it preserves growth, this technique should be recommended for early-onset scoliosis before the age of 10 years. The use of a self-expanding rod can avoid the need for repeated surgery, thereby reducing the risk of complications and the overall cost of treatment.